The process of declaring information security profiles - Potii, O.V.; Golubnychiy, D.Yu.; Vasiliev, Yu.K.; Yesina , M.V. (Radiotekhnika, 2024)
The article discusses the process of declaring information security profiles, which is an important aspect of ensuring information security in modern organizations. The main purpose of the declaration is to establish clear requirements and control measures to ensure an appropriate level of protection of information assets against potential threats and vulnerabilities. The authors of the article analyze the basic and target information security profiles, emphasizing their features, advantages and disadvantages. In particular, the basic security profile is considered as a minimum set of requirements that can be quickly implemented to ensure an initial level of protection. At the same time, the target security profile is aimed at more detailed adaptation of security measures to the specific needs and risks of the organization, which provides a higher level of protection. The process of declaring security profiles includes several stages, such as assessing the current state of security, identifying threats and vulnerabilities, defining security requirements, developing and implementing security profiles, and regularly monitoring and updating security measures. The article also discusses the current standards and regulations that govern the process of declaring security profiles, in particular, NIST SP 800-53 rev. 5, ISO/IEC 27001, and ND TZI 3.6-006-21. The article analyzes how these standards can be used to create effective security profiles that meet the specific requirements of organizations of various sizes and industries. The authors conclude that the process of declaring information security profiles is critical to ensuring an adequate level of protection of information assets. Implementation of clearly defined security profiles allows organizations to take a systematic approach to risk management, reduce the likelihood of security incidents and increase the overall level of information security.